Relationship between Work Shifts, Breastfeeding Facilities, and Family Support with Exclusive Breastfeeding Success among Working Mothers in Surabaya - Ardiansyah, Qonita Rizka Assavina Putri; Ningrum, Astika Gita; Sulistiawati, Sulistiawati; Andarsini, Mia Ratwita (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Exclusive breastfeeding among working mothers remains a public health challenge in urban areas such as Surabaya, where work demands, shift patterns, limited breastfeeding facilities, and family support may hinder optimal breastfeeding practices. Objective: This study aimed to analyze the relationship between work shifts, availability of breastfeeding facilities, and family support with exclusive breastfeeding success among working mothers in the working area of Tenggilis Public Health Center, Surabaya City. Method: An analytic observational study with a cross-sectional design was conducted among working mothers with infants aged 7–12 months. Total sampling was applied, yielding 99 respondents. Data were collected using structured questionnaires and analyzed using Chi-square tests and multivariate logistic regression. Result and Discussion: Most mothers did not work in shift systems (56.6%), worked in facilities providing breastfeeding support (57.6%), and received family support (63.7%). Exclusive breastfeeding was practiced by 62.6% of respondents. All variables were significantly associated with exclusive breastfeeding (p < 0.05), with family support as the dominant factor (OR = 27.483; p < 0.001; 95% CI:  8.135–92.85). Conclusions: Work shifts, breastfeeding facilities, and family support were significantly associated with exclusive breastfeeding success among working mothers, with family support identified as the most influential factor